In and out of glacial extremes by way of dust-climate feedbacks - Shaffer, Gary; Lambert, Fabrice (My University, 2018)
Mineral dust aerosols cool Earth directly by scattering incoming solar radiation and indirectly by affecting clouds and biogeochemical cycles. Recent Earth history has featured quasi-100,000-y, glacial-interglacial climate cycles with lower/higher temperatures and greenhouse gas concentrations during glacials/interglacials. Global average, glacial maxima dust levels were more than 3 times higher than during interglacials, thereby contributing to glacial cooling. However, the timing, strength, and overall role of dust-climate feedbacks over these cycles remain unclear. Here we use dust deposition data and temperature reconstructions from ice sheet, ocean sediment, and land archives to construct dust-climate relationships. Although absolute dust deposition rates vary greatly among these archives, they all exhibit striking, nonlinear increases toward coldest glacial conditions. From these relationships and reconstructed temperature time series, we diagnose glacial-interglacial time series of dust radiative forcing and iron fertilization of ocean biota, and use these time series to force Earth system model simulations. The results of these simulations show that dust-climate feedbacks, perhaps set off by orbital forcing, push the system in and out of extreme cold conditions such as glacial maxima. Without these dust effects, glacial temperature and atmospheric CO2 concentrations would have been much more stable at higher, intermediate glacial levels. The structure of residual anomalies over the glacial-interglacial climate cycles after subtraction of dust effects provides constraints for the strength and timing of other processes governing these cycles.
Keywords: dust forcing; glacial-interglacial climate cycles; carbon cycling; earth system modeling